Central role of the proximal tubular αKlotho/FGF receptor complex in FGF23-regulated phosphate and vitamin D metabolism - Ai Takeshita (Nature Portfolio, 2018)
Abstract Fibroblast growth factor 23 (FGF23) plays critical roles in phosphate handling and vitamin D metabolism in the kidney. However, the effector cells of FGF23 in the kidney remain unclear. αKlotho, a putative enzyme possessing β-glucuronidase activity and also a permissive co-receptor for FGF23 to bind to FGF receptors (FGFRs), is expressed most abundantly in distal convoluted tubules, whereas it is expressed modestly in proximal tubules. Key molecular players of phosphate homeostasis and vitamin D-metabolizing enzymes are known to localize in proximal tubules. To clarify the direct function of FGF23 on proximal tubules, we ablated αKlotho or Fgfr1–4 genes specifically from these tubules using the Cre-loxP-mediated genetic recombination. Both conditional knockout mouse lines showed similar phenotypes that resembled those of systemic αKlotho or Fgf23 knockout mice. Compared with control mice, they showed significantly elevated levels of plasma phosphate, FGF23 and 1,25-dihydroxyvitamin D, ectopic calcification in the kidney and aging-related phenotypes like growth retardation, osteoporosis and shortened lifespan. These findings suggest that the primary function of FGF23 on mineral metabolism is mediated through αKlotho/FGFR co-receptors expressed in proximal tubular cells, and that the putative enzymatic function of αKlotho in the proximal tubule has a minor role in systemic mineral metabolism.